PENGUATAN PENDIDIKAN KARAKTER GENERASI Z DALAM MENGHADAPI PERKEMBANGAN TEKNOLOGI DIGITAL - Atikah Nasution, Wan Nurul; Husna, Ainul; Mizkat, Eva (Smart Education, 2025)
Abstract: This community service aims to prevent negative impacts that arise due to the development of digital technology by providing counseling to students regarding strengthening character education, which is carried out at SMK Negeri 1 Tinggi Raja. The team in this activity is a team of lecturers and students from the Faculty of Teacher Training and Education, Asahan University, and lecturers from FKIP PGRI Unindra. The method used is the counseling method, namely: providing information and education to the community regarding character education, with the following steps: 1) Problem Identification, 2) Community Service Program Planning, 3) Community Service Program Implementation, 4) Evaluation, 5) Documentation, and 6) Sustainable. With this counseling activity, it provides learning to students in the generation Z category in the form of strengthening character education so that they understand the negative and positive impacts of digital technology which greatly influence their future. Keywords: character education, generation z, digital technology Abstrak: Pengabdian masyarakat ini bertujuan untuk mencegah dampak negatif yang muncul yang diakibatkan oleh perkembangan teknologi digital dengan memberikan penyuluhan kepada peserta didik mengenai penguatan pendidikan karakter, yang dilaksakan di SMK Negeri 1 Tinggi Raja. Adapun tim dalam kegiatan ini adalah tim dosen dan mahasiswa dari Fakultas Keguruan Ilmu Pendidikan Universitas Asahan, serta dosen dari FKIP PGRI Unindra. Metode yang digunakan adalah metode penyuluhan yakni: memberikan informasi dan edukasi kepada masyarakat mengenai pendidikan karakter, dengan langkah-langkah kegiatan: 1) Identifikasi Masalah, 2) Perencanaan Program Pengabdian, 3) Pelaksanaan Program Pengabdian, 4) Evaluasi, 5) Dokumentasi, dan 6) Berkelanjutan. Dengan adanya kegiatan penyuluhan ini memberikan pembelajaran kepada peserta didik kategori generasi Z berupa penguatan pendidikan karakter sehingga memahami dampak negatif dan positif teknologi digital yang sangat berpengaruh untuk masa depannya. Kata Kunci: pendidikan karakter, generasi z, teknologi digital